Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Instalasi Farmasi Rawat Jalan RSI Ibnu Sina Simpang Empat - Yustri Defni; Wahib Assyahri; Yulia Ningsih (Journal of Education on Social Science (JESS), 2023)
Ibnu Sina Islamic Hospital Simpang Empat West Pasaman is a type C private hospital that continues to progress, marked by an increase in the number of patient visits each year. The services at RSI Ibnu Sina Simpang Empat are known for the friendliness of the services provided. However, it is not uncommon for patients to complain about the lack of maximum service, one of which is in the Pharmacy Installation. This can be seen from the number of patients queuing in the Pharmacy Installation waiting room. This method uses quantitative research methods with the type of explanatory research that analyzes the relationships between a variable and other variables and tests the hypotheses that have been formulated. The population in this study were outpatients with an average monthly number of 4,886 patients obtained from the prescription record book at the Pharmacy Installation. The sample used in this study was 370 based on the Slovin Formula with a tolerance level of 5%. Sampling using simple random sampling technique.The results showed that there was a partial significant effect between tangible and patient satisfaction by 22.9%; reliability to patient satisfaction by 30.2%; empathy for patient satisfaction by 42.9%; responsiveness to patient satisfaction by 48.5%; assurance of patient satisfaction of 56.7%. And there is a stimulating influence of the five independent variables on patient satisfaction by 62.6%.